Adrenergic, Circadian, and Dietary Regulation of Interleukin-17A Expression by Adipose Gamma-Delta T Cells - Douglas, Aaron Keith (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2022)
Adipose tissue is home to a unique population of IL-17A expressing Gamma-Delta T cells (Gamma-Delta17 T cells), which are necessary for maintaining body temperature during cold environmental temperatures. However, the physiological role of adipose Gamma-Delta17 T cells in body temperature regulation and whole body metabolism during homeostatic conditions remains to be fully understood. Here, we show that wild-type adipose Gamma-Delta17 T cells display decreased effector function (IL-17A, TNF and RORyt expression), and cellular metabolism (mitochondrial ROS, mass, and membrane potential) in response to cold (4oC) environmental temperature. Core body temperature fluctuates over a 24-hour period in response to changes in the external environment, which is known as circadian rhythm. Interestingly, we observed that IL-17A expression by adipose Gamma-Delta17 T cells fluctuates over 24-hours in mice, similar to body temperature rhythm. IL-17A expression is highest at night when mice are active and feeding, and lowest during the day when mice are inactive. Administration of IL-17A in vitro and in vivo revealed a necessary role for IL-17A in regulating de novo lipogenesis gene expression in adipose tissue. Mice lacking IL-17A/F or adipocyte IL-17RC showed impaired de novo lipogenesis gene expression, which could be rescued upon administration of recombinant IL-17A/F. Crucially, impaired de novo lipogenesis in Il17a/f-/- mice disrupted circadian whole body metabolism, and body temperature maintenance. Whole body metabolic rhythm and IL-17A circadian rhythm entrain to the light cycle, but were disrupted by a high fat diet (HFD), or reverse feeding regimen. Furthermore, disruption of circadian IL-17A expression and whole body metabolic rhythm by HFD or reverse feeding increased the onset, severity and susceptibility to a mouse model of multiple sclerosis, experimental autoimmune encephalomyelitis (EAE). However, this was counteracted when mice were fed a 50% calorically restricted diet, which maintained whole body metabolic rhythm and prevented disease onset. As shift work is becoming more prevalent in modern society and is known to disturb circadian rhythm, IL-17A circadian signaling may offer a novel therapeutic route for preventing and treating diseases associated with circadian disruption, such as metabolic syndrome.
APPROVED
Keywords: IL-17A; Gamma-Delta T cells; Adipose Tissue; Thermogenesis; De Novo Lipogenesis; Circadian Rhythm; Body Temperature; High-Fat Diet; Calorie Restriction